2012
DOI: 10.1128/iai.05581-11
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 (IL-4) and IL-13 Suppress Excessive Neutrophil Infiltration and Hepatocyte Damage during Acute Murine Schistosomiasis Japonica

Abstract: Due to the importance of neutrophils and proinflammatory cytokines in schistosomal liver damage, we analyzed the mechanisms underlying neutrophil and proinflammatory responses in murine schistosomiasis japonica. We found that granulomatous inflammation around parasite eggs in the liver was greater in Schistosoma japonicum-infected IL-4 ؊/؊ IL-13 ؊/؊ (doubleknockout [DKO]) mice than in infected wild-type (WT) mice at 6 weeks, but not at 8 weeks, postinfection, suggesting the importance of Th2 responses in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 50 publications
(77 reference statements)
3
37
0
Order By: Relevance
“…It was found that during the early phase of Pseudomonas aeruginosa infection, neutrophil recruitment and cytokine (TNF-␣) and chemokine (KC) expres- sion were significantly decreased in the IL-10 transgenic mice, which resulted in impaired clearance of P. aeruginosa (32). It has been shown previously that IL-10 reduces the stability of a number of mRNAs, including KC, TNF-␣, and MIP-1 (33,34). The molecular events responsible for IL-10-mediated downregulation of MIP2 are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that during the early phase of Pseudomonas aeruginosa infection, neutrophil recruitment and cytokine (TNF-␣) and chemokine (KC) expres- sion were significantly decreased in the IL-10 transgenic mice, which resulted in impaired clearance of P. aeruginosa (32). It has been shown previously that IL-10 reduces the stability of a number of mRNAs, including KC, TNF-␣, and MIP-1 (33,34). The molecular events responsible for IL-10-mediated downregulation of MIP2 are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Given that neutrophil chemotaxis is dictated by the cytokines present in the lung, it is possible that the lower PMN numbers observed in Ja18 -/-males are due to a different cytokine environment compared to C57BL/6J mice. For example NKT cell products Il13 and Il4 (13) can reduce neutrophilia (31), possibly by inhibiting production of neutrophil chemoattractant, Il17 (32), but are both potent pro-fibrotic mediators (33,34). Thus, a higher concentration of these cytokines in Ja18 -/-mice could trigger a fibrotic response in the absence of neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-4/IL-13 signalling suppressed the excess of neutrophil accumulation in both schistosome infections, acute hepatic granuloma inflammation in mice lacking IL-4/IL-13 signalling was impaired in mansoni schistosomiasis, while being more severe in japonicum schistosomiasis, suggesting that a moderate neutrophil infiltration is required to limit the hepatic lesion in acute S. japonicum-infected mice [126]. In addition, unlike in S. mansoni infection, the mortality rate of infected mice did not increase in the absence of IL-4/ IL-13 [32,33,126,135]. Whether the Th17/neutrophil response contributes to prolonged survival and influences the development of fibrosis in S. japonicuminfected mice deserves investigation.…”
Section: Neutrophilsmentioning
confidence: 99%
“…In contrast to skin macrophages and similar to skin eosinophils, skin neutrophils did not exert a suppressive activity on the capacity of DCs to trigger T cell proliferation [65,66]. However, in models where IL-17 was associated with the pathogenicity of schistosomiasis, Th17 responses driven by an IL-23p19/IL-1β pathway favoured neutrophil recruitment/accumulation and degranulation, thereby exacerbating egg-induced tissue damage and causing mortality in acute infection [35,40,42,[123][124][125][126][127]. Considering the death in acute infection of mice developing IL-17-mediated pathogenicity, the contribution of neutrophils to fibrosis was not clearly addressed.…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation